Increasing SME Performance Through Quality Information Technology and Top Management Support - Iwan Kurniawan; Boge Triatmanto; Diana Zuhroh (Innovation Business Management and Accounting Journal, 2024)
This research aims to analyze the influence of information technology quality and top management support on the performance of the city of Semarang. This research contributes to providing feedback for SME managers or owners in making decisions regarding the importance of digitizing accounting, in this case, the accounting information system. This quantitative research uses an explanatory research approach guided by a questionnaire that tests the relationship and influence between research variables. Data analysis was obtained using the SEM approach by analyzing 132 respondents who had used the accounting information system application for at least one year. The research results show that the quality of information technology use and top management support significantly affect SME performance. The implication of this research underscores the importance of investing in improving the quality of information technology and top management support for the performance of small and medium-sized enterprises (SMEs) in Semarang City. It indicates that the utilization of effective accounting information systems and active support from top management can enhance the competitiveness and operational efficiency of SMEs. Therefore, SME managers or owners need to consider adopting and optimizing accounting information systems in their strategic decision-making processes to enhance business performance and growth.